Evaluating the factors influencing the employment of fresh graduates in Malaysia using DEMATEL and TOPSIS method / Wardah Sakinah Mohd Haris - Mohd Haris, Wardah Sakinah (2024)
This research focuses on evaluating the significant factors influencing the employment of fresh graduates in Malaysia and ranking the in-demand fields of study. This research aims to identify the factors that may influence the employment of fresh graduates. Additionally, the research aims to evaluate the significant factors that may influence the employment of fresh graduates by using the DEMATEL method and to rank the indemand fields of study by using the TOPSIS method. From the research done, the significant factors have been evaluated and the most important factor obtained is technical skills. The fields of study had also been ranked based on the demands of the industries in Malaysia. The field that has been ranked first based on the result obtained is the field of Engineering, Manufacturing and Construction. The findings of this study have provided valuable insights in terms of the significant factors and the ranks of the study fields. This study may enhance the employability of future fresh graduates of Malaysia.